Carrières d'halieutes - Gascuel, Didier (éditions Quae, 2020)
Who never dreamed of traveling the world and being in the thick of it? to fly over the Red Sea in a helicopter or to cross Algeria in search of fishing sites? For ambitious, what about being promoted to consultant in Iran, government commissioner? For combative, what if in Brussels you dedicated your nights to angry fishermen? For those who like a challenge, what if tomorrow under a scorching sun you were appointed general secretary of an industrial fishing shipowners union in the Congo to work miracles? For diplomats, what would you do if the President of the Central African Republic asked you to build a 2,000 km long pipeline to raise sea prawns in the middle of the forest? For humanitarian souls, would you be willing to play Santa Claus through a country at war? All these experiences were lived by men from whom nothing at the outset could have suggested such odysseys. Yet they all have in common a love of the sea and aquatic resources; they chose the "halieutic" specialization offered by the Rennes agronomic school.